Oral history interview with Bill (William Lawrence) Smith, March 23, 2000 - Smith, Bill (Valdosta State University Archives and Special Collections, 2000)
Oral history interview with Bill (William Lawrence) Smith, March 23, 2000. Valdosta (Ga.). Fieldworker: Marneth Andagan. Audio file digitized from cassette tape. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Topics include music and Civil War reenactments. Notes: Student paper for spring 2000, Laurie Sommers, instructor. Student paper on file. Also a member of the Rebelaires which plays for Civil War re-enactments and Sons of Confederate Veterans events, and the Georgia Volunteer Fife and Drum
1 electronic record(s) and derivatives. 1 audio file (wav, mp3) 661359418 bytes. 00:38:16. 4 PDF documents (8 scans, jp2).
Keywords: Georgia; Oral histories; Sound recordings; Musicians; Historical reenactments; American Civil War (United States : 1861-1865); Old-time music; Valdosta (Ga.); Waycross (Ga.)